Milhos com diferentes texturas de endosperma e adição de alfa-amilase na ração de leitões - Piovesan, Vanessa (2009)
Two commercially available corn varieties of different kernel texture were planted to determine their physical and chemical characteristics. The effects of corn varieties and amylase supplementation on nutrient digestibility and piglet s performance were also studied. Twelve castrated piglets weighing initially around 8 kg were individually housed in metabolic crates to determine nutrient digestibility of three experimental diets: 1) semi dent corn kernel; 2) flint corn kernel, and 3) flint corn kernel + amylase. The performance of piglets was also studied using 75 animals weighing around 8 kg distributed in randomized block design with three treatments and five replications. The treatments studied were the same used in digestibility study. In both corn kernels the chemical characteristics were similar and no different from average values found in others studies. The semi dent corn kernel had lower vitreousness index then flint corn kernel (69.3 and 74.6%, respectively), lower density (1.217 and 1.232 g/cm3, respectively) and lower 1,000-kernel weight (339.5 and 345.0 g, respectively). The protein amount of hard endosperm was higher in the flint than semi dent corn kernel. The results of electronic micrograph have indicated differences in qualitative characteristics of starch structures between corns studied. There was effect of treatments in digestible (DE) and metabolisable energy (ME) of diets being semi dent corn kernel diet had more DE and ME values than flint dent corn kernel diet. The amylase addition increased the DE and ME in flint dent corn diet. The corn kernel characteristics have no influenced feed intake, body gain and feed conversion. Amylase addition has no affected the performance characteristics studied. In conclusion there were differences in physical and chemical characteristics between corn kernels evaluated and diets with semi dent corn kernel have more DE and ME in comparison with flint corn kernel diets, although amylase addition increased energy values of flint corn kernel